STRATEGI PERUSAHAAN E-COMMERCE MEMBANGUN BRAND COMMUNITY DI MEDIA SOSIAL DALAM MENINGKATKAN OMSET PENJUALAN - Srisadono, Wahyu (Universitas Prof. Dr. Moestopo (Beragama), 2018)
E-commerce is a contact of trade transactions between the seller and the buyer by using internet media. The advantage gained by using transactions through E-commerce is to increase revenue by using online sales that are cheaper and also at the same time operational costs such as paper, catalog printing can be minimized. Big online business companies in Indonesia, such as bukalapak.com, olx.co.id, lazad.com, and the like have started to reap profits. Online business becomes an exciting business, not just for its founders, but for users, as well as buyers. To increase sales turnover E-commerce company utilize brand community in social media in face of increasingly competitive competition, main factor in brand community is formation of communication. The communication relationship does not need to be active, but at least its existence can be determined. This means that the communication that occurs can be through social media.